P2.012 Clinical Care Pathways Using Chlamydia and Gonorrhoea Tests Are Evolving: Point of Care Nucleic Acid Amplification Tests May Reduce Genitourinary Medicine Service Delivery Costs. (13th July 2013) - Adams, E J; Ehrlich, A; Turner, K M E; Shah, K; Macleod, J; Goldenberg, S; Pearce, V; Horner, P J
Abstract : Background: We aimed to explore new patient pathways using a chlamydia/gonorrhoea (CT/NG) point of care nucleic acid amplification tests (POC NAAT), and estimate and compare the costs of the new pathways to the current pathways using standard laboratory-based NAAT testing. Methods: A qualitative and quantitative approach was used. Focus groups were conducted with four sexual health clinics in the UK. They mapped out current pathways in which a CT/NG test was used, and then constructed new pathways using a POC NAAT. These pathways were then costed using a model built in Excel, and the cost of the current and POC NAAT pathways compared. Results: Pathways using a POC NAAT for asymptomatic and symptomatic patients and CT/NG only tests were shorter and less expensive than most of the current pathways (average savings of £6–8 per pathway if the POCT costs £18 per test). Clinicians identified several potential benefits to introducing the test including faster time to treatment, more accurate diagnosis of symptomatic patients, and therefore less syndromic management, which is likely to result in better care for patients. Several theoretical risks and limitations were identified in the workshops although these were not assessed in the study. Conclusion: A point of care test could be introduced to services and reduce current costs, and may mean more appropriate and quicker care for positive patients.